Maximum Dissipation Non-Equilibrium Thermodynamics and its Geometric Structure - Haslach Jr., Henry W. (Springer New York : Imprint: Springer, 2011)
Maximum Dissipation Non-Equilibrium Thermodynamics and its Geometric Structure explores the thermodynamics of non-equilibrium processes in materials. The book develops a general technique to construct nonlinear evolution equations describing non-equilibrium processes, while also developing a geometric context for non-equilibrium thermodynamics. Solid materials are the main focus in this volume, but the construction is shown to also apply to fluids. This volume also:    •             Explains the theory behind a thermodynamically-consistent construction of non-linear evolution equations for non-equilibrium processes, based on supplementing the second law with a maximum dissipation criterion  •             Provides a geometric setting for non-equilibrium thermodynamics in differential topology and, in particular, contact structures that generalize Gibbs  •            Models processes that include thermoviscoelasticity, thermoviscoplasticity, thermoelectricity and dynamic fracture  •            Recovers several standard time-dependent constitutive models as maximum dissipation processes  •            Produces transport models that predict finite velocity of propagation  •            Emphasizes applications to the time-dependent modeling of soft biological tissue  Maximum Dissipation Non-Equilibrium Thermodynamics and its Geometric Structure will be valuable for researchers, engineers and graduate students in non-equilibrium thermodynamics and the mathematical modeling of material behavior.